Philosophy in the referent: cultural-rhetoric communicative code and perlocution in "Zurita" of Leopoldo Alas "Clarín" - Albaladejo, Tomás (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper deals with the presence and function of philosophical elements within the referent of literary works. An analysis of the long short story Zurita of Leopoldo Alas “Clarín” is carried out in order to demonstrate the importance of that function starting from the referent and from the intensionalisation of the philosophical elements in the construction of a cultural-rhetorical communicative code and in the perlocutionary effect on the readers. Since the philosophical referential elements are cultural ones, the methodological perspective of Cultural Rhetoric is used and tested in this analysis.